Effect of Magnetic Field on Argon Plasma Properties - Hussein, Mohammed Ubaid (Darul Yasin Al Sys, 2025)
This study investigates the influence of an external magnetic field on the fundamental properties of argon plasma, with a specific focus on electronic and ionic densities. Experimental results obtained under varying magnetic field intensities demonstrate a significant impact on plasma behavior. The application of a magnetic field resulted in a notable increase in both electronic and ionic densities, with electronic density rising by approximately 20% and ionic density by 6%, indicating a direct proportional relationship with the strength of the magnetic field. These findings also suggest alterations in the characteristics of the electric field within the plasma environment. The results underscore the magnetic field's role in modulating plasma parameters and provide insights that may inform the design and optimization of plasma-based systems in both research and industrial contexts.